2013
DOI: 10.1186/1756-3305-6-356
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-dependent transactivation of miRNA genes following Toxoplasma gondii infection in macrophage

Abstract: BackgroundThe apicomplexan parasite Toxoplasma gondii can infect and replicate in virtually any nucleated cell in many species of warm-blooded animals; T. gondii has elaborate mechanisms to counteract host-cell apoptosis in order to maintain survival and breed in the host cells.MethodsUsing microarray profiling and a combination of conventional molecular approaches, we investigated the levels of microRNAs (miRNAs ) in human macrophage during T. gondii infection. We used molecular tools to examine Toxoplasma-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…Initial global analysis of host miRNA expression following T. gondii infection showed upregulation of 8.3% and downregulation of 4.3% of miRNAs in human macrophages . Also, a subset of miRNAs (miR‐30c‐1, miR‐125b‐2, miR‐23b‐27b‐24‐1 and miR‐17~92 cluster genes) was induced following infection of human macrophages with all three archetypal T oxoplasma strains . Examination of miRNA expression profiles in human neuroepithelioma cells with Toxoplasma infection revealed an upregulation of miR‐132, which is associated with dopamine receptor signalling in the neuropathological processes of infection .…”
Section: Changes In Host Mirna Level Following Toxoplasma Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial global analysis of host miRNA expression following T. gondii infection showed upregulation of 8.3% and downregulation of 4.3% of miRNAs in human macrophages . Also, a subset of miRNAs (miR‐30c‐1, miR‐125b‐2, miR‐23b‐27b‐24‐1 and miR‐17~92 cluster genes) was induced following infection of human macrophages with all three archetypal T oxoplasma strains . Examination of miRNA expression profiles in human neuroepithelioma cells with Toxoplasma infection revealed an upregulation of miR‐132, which is associated with dopamine receptor signalling in the neuropathological processes of infection .…”
Section: Changes In Host Mirna Level Following Toxoplasma Infectionmentioning
confidence: 99%
“…Many innate immune effectors are controlled by host cell signalling, followed by regulating the overall response to invading protozoa and influencing the consequences of infection. The successful parasite T. gondii may subvert host cell immune pathways as one of its survival strategies …”
Section: Altered Cell Signalling Following Toxoplasma Infection May Bmentioning
confidence: 99%
“…Acute T. gondii infection initiates M1-dominant polarization of macrophages, which produce high levels of NO and proinflammatory cytokines such as TNF-α and IL-622232829. M1 macrophages destroy intracellular pathogens by releasing NO, which is known to be a major effector molecule in macrophage-mediated cytotoxicity27.…”
Section: Resultsmentioning
confidence: 99%
“…Cai reported that STAT3 mediates a prosurvival pathway by upregulating miRNAs, leading to inhibition of host cells with Toxoplasma infection. Thus, the function of STAT3-binding miRNAs is considered to be an essential apparatus in Toxoplasma biology 49 . Liu et al .…”
Section: Involvement Of Stat3 In the Pathogenesis Of Virus Infectionmentioning
confidence: 99%